ANALISIS TINGKAT KESEHATAN BANK DENGAN METODE RGEC PADA BANK MEGA SYARIAH TAHUN 2018 – 2023 - Wiyati, Rita; Salmiah, Neneng; Wibisono, Rafidianto; Andira, Agung Putra (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2024)
This research aims to determine the level of bank health at Bank Mega Syariah in 2018 - 2023. The type of research used is descriptive research with a quantitative approach. The indicator used is the RGEC Composite Rating obtained by. The ratios used consist of the NPF, FDR, GCG-Self Assessment, ROA, ROE, BOPO and CAR ratios. The research results show that Bank Mega was able to improve its health ranking, initially in 2018 - 2019 it was ranked 2 (healthy) but in 2020 - 2023 it experienced an increase so it was ranked 1 (Very Healthy), Keywords: